Diatoms and invertebrates as indicators of pH in wetlands of the south-west of Western Australia - Thomas, Erin J (Curtin University, 2007)
Increased groundwater usage, rainfall decline and activities such as mining have resulted in the acidification of certain wetlands in the south-west of Western Australia. This study investigated the influence of pH, the factor most commonly associated with acidification, on the invertebrate and diatom community structure of 20 wetlands in the south-west region of Western Australia. Few studies in Western Australia have investigated both biotic groups, particularly in relation to pH. Consequently, this study examined the comparative sensitivity of the two biotic groups to pH in order to identify the most effective biotic tool for assessing the ecological impacts of pH decrease. The wetlands included in this study displayed a wide range of pH from acidic (pH < 6.5) to alkaline (pH > 7.5). Other environmental parameters were also variable. Separation of the wetlands into three pH groups; Group 1 – acidic, Group 2 – circumneutral and Group 3 – alkaline, demonstrated that the acidic Group 1 wetlands generally had higher electrical conductivity than the remaining groups. This was probably due to the association of many Group 1 sites with mining and acid sulphate soils. Seasonal trends in environmental variables across the three pH groups were mostly unclear although some trends were evident within the individual pH groups. The study showed that invertebrate community structure differed in response to pH. However, the results also demonstrated that invertebrate distribution patterns were influenced by other factors.Potential indicator species identified from the study included Macrothrix indistincta and Tanytarsus fuscithorax/semibarbitarsus which were abundant in acidic waters and Alona quadrangularis which was common in circumneutral sites. Taxa such as Calamoecia tasmanica subattenuata were common over a wider range of pH (acidic to circumneutral) but may still have potential to act as indicators of pH decline. Diatom community structure was also shown to be influenced by pH, with the variable identified as a major determinant of diatom distribution patterns. Nitzschia paleaeformis and Navicula aff. cari were generally recorded from acidic wetlands and are potentially useful as indicators of low pH conditions. Brachysira brebissonii and Frustulia magaliesmontana were also identified as species with the potential to indicate pH decline. In contrast, taxa including Gomphonema parvulum, Staurosira construens var. venter and Nitzschia palea were generally associated with moderate to high pH levels. A comparative study of the two biotic groups using multivariate analyses revealed that diatoms were more sensitive to pH than invertebrates. Further investigation with a larger number of environmental variables would be necessary to ascertain the other factors primarily influencing invertebrate community structure. Nonetheless, the findings imply that diatoms and invertebrates differ in their responsiveness to various environmental factors and may provide complementary information on the integrity of a system. Multivariate analyses on an expanded data-set of 40 sites found that pH accounted for the greatest amount of variation in the data and was conducive to the development of a diatom-based pH inference model.The strongest model was produced using weighted averaging (WA) with classical deshrinking. While the model displayed a high correlation coefficient, the prediction error was also relatively high, probably as a result of the comparatively small and heterogeneous data-set. Incorporation of the data into a larger training set would be likely to improve the predictive ability. Applications for the model include pH reconstructions or use in monitoring programs. The current study has shown that pH is an important variable influencing both invertebrate and diatom community structure in wetlands in the south-west of Western Australia. However, the greater sensitivity of diatoms to pH suggests that they would be the most effective tool for the biological monitoring of pH in wetlands threatened or impacted by acidification. An integrated monitoring program including both diatoms and invertebrates may provide additional information on the impacts of pH decline and the overall integrity of the systems and should be investigated further.